Comparative Performance of New Agronomic Technology on the Yield Potential of Groundnuts (Arachis hypogaea L.) under Rainfed Agriculture in Guruve District, Zimbabwe - Lawrence Mango; Savo Memory; Kampiyau Danie (Universitas Andalas, 2022)
The study was carried out to assess the yield performance of groundnuts grown on ridges and non-ridges by communal farmers of ward 8 in the Guruve district of Mashonaland Central province, Zimbabwe. Interviews, surveys, questionnaires, and observation methods were used for data collection. A sample of 60 respondents was selected from a list of groundnut farmers in the ward. The results showed that 43% of the respondents were growing groundnuts on ridges, while 57% of the respondents were growing groundnuts on non-ridges. No farmers used both farming practices. The results showed that more yield per hectare was obtained by farmers who used ridged farming practices than nonridging techniques. The area planted with groundnuts varied significantly (P<0.001) with the farming practice (ridging and nonridging) and the farming seasons. The rate of adoption of the ridging farming technology was affected by the age of the household head, level of education of the household head, sex, and age of the household head. More females participated in the growing of groundnuts than their male counterparts. In conclusion, groundnut yield was comparatively higher on ridged farming technology than on non-ridging technology; farmers are encouraged to plant groundnuts on ridges to cherish the highest production benefits. However, more training is needed for farmers to take upon new farming technology and regard groundnuts as a cash crop rather than a women's crop as well as to improve the household income.